PERSEPSI KEUNTUNGAN DAN TINGKAT KEPERCAYAAN DALAM MEDIA SOSIAL SEBAGAI DETERMINAN INTENSI UMKM DENGAN KENYAMANAN SEBAGAI VARIABEL INTERVENING - Ikhsan Habib Fabillah; Erni Febriani; Ayu Aulia; Silvia Prisca Gani (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2026)
This study aims to explore the impact of perceived benefits and perceived trust on MSMEs' intention to transact on social media platforms, with perceived convenience as a mediating variable. The methodology used is a quantitative approach by conducting a survey of 292 MSMEs in Lampung Province who actively use social media for transactions. The data obtained were analyzed through Structural Equation Modeling with the Partial Least Squares (PLS-SEM) approach. The findings of this study indicate that both perceived benefits and perceived trust have a positive and significant influence on perceived convenience. In addition, perceived benefits, perceived trust, and perceived convenience also have a positive and significant influence on MSMEs' intention to transact through social media. The results indicate that perceived convenience functions as a partial mediator for the influence of perceived benefits and perceived trust on MSMEs' intention.